2020
DOI: 10.1002/jper.19-0535
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on immunophenotypic characterization and osteogenic differentiation of human mesenchymal stromal cells derived from periodontal ligament and gingiva

Abstract: Background Mesenchymal stem cells (MSCs) derived from periodontal ligament (PDL) and gingiva can be used for the development of cell‐based regenerative approaches in dentistry and medicine. The purpose of this investigation was to establish a method for isolation of human stem cells from the PDL and gingiva, multilineage differentiation of those cells, and comparison of periodontal ligament mesenchymal stem cells (PDLMSCs) and gingival mesenchymal stem cells (GMSCs). Methods PDL and gingival tissues of third m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The experimental protocol was approved by the institutional review board of the Dankook University Dental Hospital, Cheonan, Korea (approval number: DKUDH IRB 2019-01-006). Human PDLSCs were isolated as described in detail in a previous report [ 41 ]. Briefly, periodontal ligament (PDL) tissue was carefully dissected from the middle third of the root with a sterilized scalpel and minced into pieces that were as small as possible.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental protocol was approved by the institutional review board of the Dankook University Dental Hospital, Cheonan, Korea (approval number: DKUDH IRB 2019-01-006). Human PDLSCs were isolated as described in detail in a previous report [ 41 ]. Briefly, periodontal ligament (PDL) tissue was carefully dissected from the middle third of the root with a sterilized scalpel and minced into pieces that were as small as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, they found that GMSCs display stable morphology and do not lose MSC characteristics and maintain telomerase activity following long-term cultures (22). In comparison to other types of dental MSCs, previous studies indicated that GMSCs possess less osteogenic potentials than PDLSCs (27,32,33). However, compared to PDLSCs, GMSCs are less susceptible to replicative senescence and proinflammatory cytokine-induced impairment in osteogenic potentials in vitro and ectopic bone formation in vivo (27).…”
Section: Isolation and Characterization Of Human Gingiva-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…A total of 26 studies were selected for the current systematic review. Of these, 20 in vitro were culture studies [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] and 6 were in vivo studies [64][65][66][67][68][69]. All papers were published in the English language, and the date of publication started in 2009.…”
Section: Characteristics Of In Vitro Included Studiesmentioning
confidence: 99%